The Effect Of Workload And Work Environment On Employee Performance In Karawang Health Service - Ara Nopita; Sari Marliani; July Yuliawati (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — This research aimed to determine the influence of workload and work environment on the performance of Karawang Health Service employees. Research method— The study employed a descriptive, quantitative, and verification approach using multiple linear regression analysis with the SPSS 25 application. Data was collected through questionnaires and interviews with 81 respondents. Result— The results showed that the workload scored high, the work environment scored average with good criteria, and employee performance scored average with good criteria. Partially, workload had a very significant effect on employee performance, while the work environment had no effect and a negative influence on employee performance. Simultaneously, workload and work environment had a very significant effect on employee performance. Conclusion— The high workload and average work environment significantly affected employee performance at the Karawang Health Service. Improving the work environment could enhance employee performance further.